2019
DOI: 10.1002/chem.201902204
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Aryl–Aryl Cross‐Coupling: C−H Arylation of 2‐Naphthols with Diaryliodonium Salts

Abstract: Transition‐metal‐free regioselecitive C−H arylation of 2‐naphthols with diaryliodonium salts has been developed. The reaction proceeds under very simple experimental conditions and affords a range of products with various substitution patterns. The method allows for the incorporation of electron‐deficient aryls, which complements well currently existing metal‐free aryl–aryl cross‐couplings of phenols that have been so far restricted to the introduction of electron‐rich aryl moieties. The mechanism of the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Recently, in 2019 Kalek group [46] reported a transition metal‐free regioselective aryl‐aryl cross‐coupling reactions of 2‐naphthols with diaryliodonium salts. The symmetrical diaryliodonium salts with electron deficient functional groups was identified as potential aryl source (Scheme 41).…”
Section: Metal‐free Aryl‐aryl Cross‐coupling Reactions Using Hypervalmentioning
confidence: 99%
“…Recently, in 2019 Kalek group [46] reported a transition metal‐free regioselective aryl‐aryl cross‐coupling reactions of 2‐naphthols with diaryliodonium salts. The symmetrical diaryliodonium salts with electron deficient functional groups was identified as potential aryl source (Scheme 41).…”
Section: Metal‐free Aryl‐aryl Cross‐coupling Reactions Using Hypervalmentioning
confidence: 99%
“…The progress in synthesis of biaryls employing diaryliodonium salts as aryl cation equivalents has made this class of bench-stable, nontoxic, and readily available reagents attract attention [ 35 , 36 , 37 , 38 , 39 ]. Moreover, copper catalyst can be oxidized in the presence of diaryliodonium salts to form a highly electrophilic aryl-Cu(III) intermediate and a range of latent nucleophiles undergo arylation reactions to form synthetically versatile products [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, only few examples are known. Quideau (Ozanne-Beaudenon and Quideau, 2005), described C-and Oarylation mixtures and Kalek (Ghosh et al, 2019) reported on the selective C-arylation of naphthols using fluorinated Ar 2 IOTf. In all these protocols, the stoichiometric use of a base is needed for the reaction giving rise to the monoarylation of naphthols by transferring one aryl group from Ar 2 IX via an ionic pathway (Oh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%